Redox-coupled substrate water reorganization in the active site of Photosystem II - the role of calcium in substrate water delivery - Ugur,I; Rutherford,AW; Kaila,VR (Biochimica et Biophysica Acta - Bioenergetics, 2016)
Photosystem II (PSII) catalyzes light-driven water splitting in nature and is the key enzyme for energy input into the biosphere. Important details of its mechanism are not well understood. In order to understand the mechanism of water splitting, we perform here large-scale density functional theory (DFT) calculations on the active site of PSII in different oxidation, spin and ligand states. Prior to formation of the O-O bond, we find that all manganese atoms are oxidized to Mn(IV) in the S3 state, consistent with earlier studies. We find here, however, that the formation of the S3 state is coupled to the movement of a calcium-bound hydroxide (W3) from the Ca to a Mn (Mn1 or Mn4) in a process that is triggered by the formation of a tyrosyl radical (Tyr-161) and its protonated base, His-190. We find that subsequent oxidation and deprotonation of this hydroxide on Mn1 result in formation of an oxyl-radical that can exergonically couple with one of the oxo-bridges (O5), forming an O-O bond. When O2 leaves the active site, a second Ca-bound water molecule reorients to bridge the gap between the manganese ions Mn1 and Mn4, forming a new oxo-bridge for the next reaction cycle. Our findings are consistent with experimental data, and suggest that the calcium ion may control substrate water access to the water oxidation sites.